The water–energy–food nexus at home: New opportunities for policy interventions in household sustainability. Issue 4 (7th June 2018) - Foden, Mike; Browne, Alison L.; Evans, David M.; Sharp, Liz; Watson, Matt
Abstract : The nexus of water–energy–food (WEF) is as apparent at the household scale as it is anywhere else. We introduce the "Nexus at Home" as a starting point for exploring the dynamics of WEF resource use and household sustainability. Drawing on two research projects we focus specifically on domestic kitchens as a site where practices of cooking, eating, cleaning and disposing of waste come together. While these practices have long been targets for policy intervention, existing approaches draw on a limited range of perspectives from the social sciences. Reflecting on our work with four non‐academic partners (Defra, BEIS, FSA, Waterwise), we consider how social practice and geographies of household sustainability research might be combined with the dictum of "nexus thinking" to re‐imagine the framing of policy and intervention to reduce the resource intensity of everyday life. Synthesising existing "home practices" literature in the context of the "live" policy problems raised by our partners, we seek to provide clear guidance for intervening in kitchen practices. We draw on one topic which has not yet been the subject of social practices research: fats, oils and grease (FOG) going down the kitchen plughole and contributing to widespread sewer blockages. In doing so we document the sequence of interrelated food provisioning activities through which WEF is put to use in domestic kitchens and contributes to FOG blockages in sewers. We reflect upon the multiple ways these practices are shaped by the rhythms of daily life, dynamics within the home, wider cultural conventions, and infrastructures. This paper contributes to the nascent transdisciplinary research agenda of translating home practices research into wider conceptualisations of "intervention, " with a specific orientation towards academic and non‐academic stakeholders who are interested in influencing systems of sustainable consumption and production within, and across, the WEF sectors.